KOMUNIKASI TERAPEUTIK DI KLINIK NU LUMAJANG DALAM PERSPEKTIF ISLAM - Rio Febriannur Rachman; Abdul Hakim (Metakom, 2020)
This article examines how the application of therapeutic communication in the Klinik NU Lumajang (clinic whish is possessed by Nahdlatul Ulama or NU organization) based on Islamic perspective. The majority of patients in this clinic are Muslims, so the population of Lumajang, as the target of this clinic. The purpose of this study is to describe the therapeutic communication of nurse to the patient. This research uses qualitative method, through case study approach. Data sources are obtained from the Klinik NU Lumajang. Data collection techniques are observation, interview or personal communication, reading of literature related to the research topic. The results of this study explain, therapeutic communication of nurses to patients at the Klinik NU Lumajang is carried out with several stages; the preparatory stage, the introductory stage, the work stage, and the termination stage. The reciprocal of the patient, responded by the nurse by listening carefully to the patient’s health problem. The nurse must also show acceptance of the message conveyed by the patient. Therapeutic communication can run smoothly on the seriousness of nurses, who work based on sincerity and only expect the best reply from God Almighty.